Oxidation of 4-Aryl-1,1,1-trifluorobut-2-en-2-yl Trifluoromethanesulfonates by 4-Picoline-N-Oxide: A Novel Approach to β-Trifluoromethyl-α,β-enones - Li, Dong; Lv, Shujun; Qu, Jingping; Zhou, Yuhan (Synthesis, 2020)
An efficient approach to β-trifluoromethyl-α,β-enones via oxidation of 4-aryl-1,1,1-trifluorobut-2-en-2-yl trifluoromethanesulfonates is described. The reaction proceeds smoothly under mild and metal-free conditions and tolerates a wide range of functional groups. Various β-trifluoromethyl-α,β-enones were obtained in moderate to good yields.
Keywords: fluorine; enones; oxidation; β-trifluoromethyl-α,β-enones; 4-aryl-1,1,1-trifluorobut-2-en-2-yl trifluoromethanesulfonates; pyridine N-oxides